Studi Normatif Ekonomi Syariah: Dari Perintah Al-Qur’an hingga Hukum Normatif—Rekontruksi Sejarah Larangan Riba dalam QS. Al-Baqarah 278–279 dan Implikasinya bagi Penguatan Tata Kelola Keuangan Syariah di Indonesia - Juli Daniati Lestari; Mujibu Da'wat (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2026)
Purpose - This article reconstructs the legal rationale (ratio legis) of the Qur’anic prohibition of riba in QS. al-Baqarah (2): 278–279 by integrating historical reconstruction of asbāb al-nuzul, classical Qur’anic interpretation, and contemporary Islamic economic law analysis. The study aims to (i) identify the anti-ẓulm (anti-injustice) foundation underlying the prohibition of ribā, (ii) examine its translation into Indonesia’s positive legal framework and sharia governance architecture, and (iii) evaluate contemporary compliance challenges, particularly in consumptive murabaḥah financing and digital Islamic finance. Method - This research employs doctrinal (normative) legal research using historical, conceptual, and statute approaches. The historical analysis examines classical asbab al-nuzul narratives from al-Wahidi and al-Suyuti and interpretations of QS. al-Baqarah (2): 278–279 in major tafsir works, including al-Tabari, Ibn Kathir, al-Qurtubi, al-Razi, and al-Jassas. The conceptual approach analyses riba, zulm, maqasid al-shari'ah, sadd al-dhara'i', al-ghunm bi al-ghurm, and the substance-over-form approach. The statute approach examines Law No. 4 of 2023 concerning Financial Sector Development and Strengthening (P2SK), POJK No. 2/2024, POJK No. 25/2024, and relevant DSN–MUI fatwas. Result - The findings demonstrate that QS. al-Baqarah (2): 278–279 should not be understood merely as a prohibition of additional monetary gain, but as a normative correction against exploitative financial structures. The phrase “la tazlimuna wa la tuzlamun” reflects the central objective of preventing injustice, unilateral risk transfer, and economic domination in creditor–debtor relations. The study further finds a normative gap between this anti-zulm principle and contemporary sharia finance practices, particularly where formal contractual compliance may coexist with economic effects resembling interest-based transactions. Consumptive murabahah structures and digital financing mechanisms involving fees, penalties, and information asymmetry represent critical areas requiring substantive compliance assessment. Implication - This study proposes an Anti-Zulm Compliance Framework as an operational model for strengthening sharia governance in Indonesia. The framework emphasizes measurable substance testing through risk-based sharia audits, transparency of financing costs, fair risk allocation, prevention of sharia arbitrage, and corrective governance mechanisms. The findings suggest that Islamic financial regulation should move beyond formal contract validation toward a substantive compliance approach that aligns financial practices with the maqasid-oriented objective of justice and protection of wealth (hifz al-mal).